Kemampuan Keterampilan Proses Sains Dan Hasil Belajar Mahasiswa Pendidikan Biologi Fkip Ums Pada Mata Praktikum Fisiologi Pertumbuhan Dan Perkembangan Tanaman Tahun Akademik 2016/2017 - Tania, Tantri; , Dra. Aminah Asngad, M. Si (2017)
The course of Physiology of Plants' Growth and Development is a compulsory subject for the students of Biology Education Department, FKIP, UMS. It takes 1 credits. This lab course contains the lab skills that have been mastered by the students. Practical skills are absolutely expected to be related to outcomes. This study aims to know the ability of Science Process Skill and outcomes of the fourth semester students of Biology Education Department, FKIP, UMS. This research is a expostfacto research which is conducted in February 2016 to March 2017. The subject of the research is the fourth semester students of Biology Education Department of FKIP,UMS in the academic year of 2016/2017 who take the course of Physiology of Plants' Growth and Development Programs who numbered 138 students. The results of this research show that the average of each aspect of science process skills with max average is 4. Obtained from the observation aspect is 3.92, the average of using tools and materials is 3.95, the average of data interpretation 3.36, and the average of communication aspects in writing is 3,30. The highest result of science process skill is on the aspects of using tools and materials, while the lowest results of science process skill is on written communication aspect. While the average outcomes is 81,11 and average value of science skill process is 90,89. The results shows that value of science skill process more than outcomes. Based on analysis results there is the correlation of science process skill to the student's outcomes of Biology Education Department, FKIP UMS Academik Year 2016/2017. Keywords : science process skills, outcomes, physiologi of plants.